Digging in: impact of land use changes on soil aggregation patterns and carbon stocks in the moist tropics of the Mizoram in the Indomalayan realm - Chowlani Manpoong; Tripathi, Shri Kant; Aravindakshan, Sreejith; Krupnik, Timothy J. (Elsevier, 2025)
Land use change in moist tropical regions can significantly affect soil stability and carbon stocks, particularly with the conversion from primary forests. This study investigated the effects of land-use on soil aggregation and associated carbon stocks. A total of 200 soil samples were collected across five land-use, comprising rubber (RP) and oil palm plantations (OPP), bamboo forests (BF), fallow land (FL), and natural forest (NF). A comprehensive land-use intensity index, encompassing six key dimensions of land-use change, was integrated into robust regression models. The soil analyses revealed that macroaggregates dominated the top 15 cm (51–64 %), followed by meso- (30–39 %) and microaggregates (6–12 %). At deeper depths (15–30 cm), mesoaggregates prevailed (45.3–52.1 %). NF and BF exhibited the highest microaggregate fractions, resulting in lower mean weight diameter (MWD) and potentially lower aggregate stability. In contrast, RP and OPP displayed the highest macroaggregate distribution and MWD. Soil organic carbon generally decreased with land-use change from NF to FL and plantations, except for RP. MWD significantly correlated with silt and clay content, while meso- and micro-aggregates correlated with silt/clay content, MWD, and nitrogen (N). Models revealed that land-use intensity, bulk density, porosity, and N significantly influenced soil aggregate size. Notably, land-use intensity was lower in NF, BF, and FL compared to plantations (RP and OPP). The findings highlight the critical impact of land-use change in moist tropical regions on soil aggregation and carbon stocks, crucial for assessing the environmental consequences of converting natural forests to agricultural plantations. The study advances knowledge by introducing a comprehensive land-use intensity index, providing insights for sustainable land management and climate action. However, the findings are region-specific, and long-term experimentation and monitoring are needed to fully understand the effects of land use change on soil.